Advanced Unified Earthquake Catalog for North East India - Pallavi; Ranjit Das; Sandeep Joshi; Claudio Meneses; Tinku Biswas (Applied Sciences, 2023)
Northeast India is one of the world’s most seismically active regions. The event data included in this research for the period 1737–2012 is mostly obtained from worldwide database agencies such as ISC, NEIC, and GCMT. Historical seismicity is collected from published and unpublished documents and some earthquake events are collected from the Indian Meteorological Department Bulletins. As the Mw scale is developed and validated in the southern California region and overestimates the smaller magnitude earthquakes, therefore, recent literature suggested an improved version of the seismic moment magnitude scale (Mwg) applicable for the entire globe considering both long- and short-period frequency-spectra using modern instrumental data. To update the earthquake catalog of Northeast India, we prepared empirical relationships between different magnitudes to Mwg using robust statistical General Orthogonal Regression. A procedure is also suggested for converting different earthquake sizes towards seismic moment scale. The Magnitude of Completeness (Mc) and the Gutenberg–Richter (GR) recurrence parameter values for the declustered homogenized catalog in four time periods, namely 1737–1963, 1964–1990, 1964–2000, and 1964–2012, have been computed. Our analysis suggests that the use of the Mwg scale improves seismicity parameters ‘b’ up to 30%, ‘a’ up to 17%, and ‘Mc’ up to 18% for the Northeast India region. A complete unified earthquake catalog in terms of advanced seismic moment magnitude scale could help understand seismicity and earthquake engineering studies of the region.